2017
DOI: 10.3892/ol.2017.6746
|View full text |Cite
|
Sign up to set email alerts
|

miR-21 inhibition of LATS1 promotes proliferation and metastasis of renal cancer cells and tumor stem cell phenotype

Abstract: MicroRNA (miR)-21 has many regulatory functions in the cell, including activities in cancer cells and cancer stem cells. Large tumor suppressor gene 1 (LATS1) is a target of miR-21 that could mediate several of these phenotypes. This study explored the effect of miR-21 silencing in renal cancer cell function and LATS1 expression. Silencing of miR-21 in Caki-2 cells reached an efficiency of 55–60%. This was sufficient to detect decrease in Caki-2 cell proliferation and migration invasion capacity. miR-21 silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…miR-21 is involved in epigenetic regulation of YAP1 at two levels: i) miR-21 suppression results in elevated levels of LATS1/2, which down-regulates YAP through phosphorylation [ 13 ]; ii) computational target prediction identifies homology between miR-21 and 3'-UTR of human YAP1 mRNA ( www.targetscan.org ). RT-qPCR revealed that miR-21 expression was significantly more than 3-fold increased in the muscles from DMD patients (p < 0.0001 vs control muscles).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-21 is involved in epigenetic regulation of YAP1 at two levels: i) miR-21 suppression results in elevated levels of LATS1/2, which down-regulates YAP through phosphorylation [ 13 ]; ii) computational target prediction identifies homology between miR-21 and 3'-UTR of human YAP1 mRNA ( www.targetscan.org ). RT-qPCR revealed that miR-21 expression was significantly more than 3-fold increased in the muscles from DMD patients (p < 0.0001 vs control muscles).…”
Section: Resultsmentioning
confidence: 99%
“…To validate downstream YAP pathway, Survivin (Birc5) which is one of the prominent target genes of YAP [ 3 , 12 ], and miR-21 which is involved in epigenetic regulation of YAP [ 13 ] were studied. RT-qPCR for Survivin Assay ID Hs01125524_m1 was performed using a standard TaqMan PCR kit procedure on an AB-7300 RT-PCR system (Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…(38)(39)(40)(41). As a result, inhibition of the aberrant hyperactivity of miR-21 in tumor tissue leads to global changes in cellular signaling pathways and promotes manifold reinforcement of tumor suppressor protein synthesis, such as PTEN, PDCD4, RhoB, LATS1, MGMT, and TP53, exerting potent antitumor action on several carcinogenesis processes simultaneously (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating the role of gene copy number variation in relation to the clinical parameters of metastatic CCRCC, the loss of PLG was associated with advanced tumor stage and Fuhrman grade (27). As for the hub miRNAs, miR-21 has been widely studied in renal cancer for its regulatory roles in cellular proliferation and metastasis (2830). In addition, the hub miRNA, miR-155, was determined to regulate the growth and invasion of CCRCC cells by interacting with E2F transcription factor 2 (31).…”
Section: Discussionmentioning
confidence: 99%